Pengaruh Pemberian Jus Wortel terhadap Penurunan Disminore pada Remaja di Desa Ngablak - Diah Ajeng Pratiwi; Kamidah Kamidah (Calory Journal Medical Laboratory Journal, 2024)
Background: Dysmenorrhea is pain experienced during or just before menstruation and is one of the most common gynecological issues affecting women of all ages. Primary dysmenorrhea occurs 6 to 12 months after the first menstruation and is caused by high levels of prostaglandins released from endometrial secretions, leading to painful uterine contractions. Carrots are a vegetable rich in vitamin E, which can help block the formation of prostaglandins and counteract the effects of increased production of prostaglandin hormones. Objective :To analyze the difference in dysmenorrhea pain levels before and after consuming carrot juice. Method : A one-group pretest-posttest approach was used, conducted in Ngablak Village, Kenteng Nogosari, Boyolali, in April-May, involving 20 respondents. Data processing was done using the Wilcoxon statistical test. Results: The majority of respondents before consuming carrot juice (100%) experienced severe pain. After consuming carrot juice, out of 20 respondents (100%), 6 (30.0%) experienced a reduction to mild pain, and 14 (70.0%) experienced a reduction to moderate pain. The Wilcoxon test results showed a significant effect of carrot juice on dysmenorrhea in adolescents, with a p-value of 0.00 (p < 0.05). Conclusion: There is an effect of consuming carrot juice on the reduction of dysmenorrhea in adolescents in Ngablak Village.